Different Forms of Digital Marketing: A Comprehensive Analysis - Perry Gamba (International Journal of Marketing and Digital Creative, 2025)
This study provides a comprehensive examination of the various forms of digital marketing and their strategic applications in contemporary business environments. Through an extensive review of existing literature and qualitative research involving semi-structured interviews with industry experts in Uganda, this research offers profound insights into the diverse digital marketing strategies employed by modern businesses. The findings identify and elaborate on five primary forms of digital marketing: search engine optimization (SEO), social media marketing, email marketing, content marketing, and pay-per-click (PPC) advertising. Each form is analysed in detail, highlighting its unique advantages, applications, and contribution to a holistic digital marketing strategy. For practitioners in digital creative industries, these findings offer actionable frameworks to navigate platform-specific challenges, optimize content creation workflows, and measure cross-channel performance in increasingly competitive digital ecosystems.  This study makes a significant contribution to the existing body of knowledge by providing a detailed and expanded analysis of various digital marketing forms and their practical applications, with a particular focus on their relevance and applicability in emerging markets. The paper concludes with actionable recommendations for practitioners and outlines future research directions in the ever-evolving digital marketing landscape.